Holistic gynecological care of the patient after hysterectomy for malignant endometrial cancer - Gzowska, Daria; Szablewska, Anna W. (Nursing Problems / Problemy Pielęgniarstwa, 2025)
Malignant endometrial cancer is the most common gynecological condition. It is most often diagnosed among peri-menopausal women. An increase in incidence and mortality is seen especially in developed countries, where an increased trend toward obesity and diabetes is noted. High-quality and effective care of the patient with endometrial cancer is possible primarily through the educational role of the midwife, who can help the patient understand the current activities and recommended methods of care. The paper introduces the topic of endometrial cancer and the hysterectomy procedure, and presents a holistic approach in the perioperative period based on an individual case study created based on CARE guidelines on the basis of ICNP (International Classification for Nursing Practice) reference terminology enriched with ICF (International Classification of Functioning, Disability and Health) using C-HOBIC (Canadian Health Outcomes for Better Information and Care) care outcome indicators. The most significant finding is that, in addition to appropriately selected clinical treatment, a comprehensively planned nursing care approach that includes both medical and psychological aspects is equally important.